Anna Piaggi, Aby Warburg and the Judgement of Paris, 2011. (1st October 2017) - Clark, Judith
Judith Clark looks at fashion exhibition-making alongside Aby Warburg's Mnemosyne Atlas (Panel 55) for her 2011 gallery exhibition entitled The Judgement of Paris. By looking at the three goddesses' attributes, the reproduced exhibition leaflet wonders about the styling of mannequins and props that are intrinsic to exhibition-making but extrinsic to the exhibited object (namely dress), which is omitted from the exhibition entirely. The visual essay links Aby Warburg to Anna Piaggi's monthly collages for Vogue Italia and their idiosyncratic act of recovery.